A cross-sectional study of patterns of airway dysfunction, symptoms and morbidity in primary care asthma. - Shaw, D; Green, R; Berry, M; Mellor, S; Hargadon, B; Shelley, M; McKenna, S; Thomas, M; Pavord, I (2012)
BACKGROUND: Most patients with asthma are managed exclusively in primary care. Little is known about the patterns of airway dysfunction in these patients and how these relate to other aspects of the disease. AIMS: We set out to assess this in a cross-sectional study of 262 patients. METHODS: Symptoms, spirometry, airway responsiveness, reversibility, and airway inflammation were all assessed. Exacerbations requiring oral corticosteroids in the preceding year were enumerated. RESULTS: Patients had heterogeneous patterns of airway dysfunction. Those with a post-bronchodilator forced expiratory volume in 1 sec/ forced vital capacity ratio of <0.7 had more exacerbations in the previous year (2.2 vs. 0.8; mean difference 1.4; 95% CI 0.4 to 2.4; p=0.007). Patients with normal results had less inflammation (proportion with a sputum eosinophil count of >1.9%, 20% vs. 48%, χ²=14.8, df=3; p<0.001) and fewer exacerbations (0.5 vs. 1.4; mean difference -0.9; 95% CI -1.4 to -0.4; p=0.001) but similar symptom scores (6.2 vs. 6.9; p=0.2) compared with patients with any abnormality. CONCLUSIONS: Patients with a diagnosis of asthma have mixed patterns of physiological impairment; many have no airflow obstruction or airway hyper-responsiveness. The physiological characterisation of asthma is not related to symptoms and is of little value in predicting exacerbations or eosinophilic airway inflammation.